2021
DOI: 10.7717/peerj.12639
|View full text |Cite
|
Sign up to set email alerts
|

Variation in global distribution, population structures, and demographic history for fourTrichiuruscutlassfishes

Abstract: Background Species-specific information on distribution and demographic patterns provides important implications for conservation and fisheries management. However, such information is often lacking for morphologically-similar species, which may lead to biases in the assessments of these species and even decrease effort towards sustainable management. Here, we aimed to uncover the distribution range, population structure and demographic history for four exploited Trichiurus cutlassfishes using g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 71 publications
3
9
0
Order By: Relevance
“…Thus, our study considers these two groups might be T. nanhaiensis and T. gangeticus, although we did not collect the COI data of T. nanhaiensis in the east Indian Ocean. In addition, our study found some specimens from the Gulf of Oman referred to in Lin et al (2021) were in fact T. lepturus. However, T. lepturus had the highest intraspecific diversity (Table 2).…”
Section: Systematics Of Trichiurussupporting
confidence: 48%
See 2 more Smart Citations
“…Thus, our study considers these two groups might be T. nanhaiensis and T. gangeticus, although we did not collect the COI data of T. nanhaiensis in the east Indian Ocean. In addition, our study found some specimens from the Gulf of Oman referred to in Lin et al (2021) were in fact T. lepturus. However, T. lepturus had the highest intraspecific diversity (Table 2).…”
Section: Systematics Of Trichiurussupporting
confidence: 48%
“…Jahromi et al (2016) examined the phylogenetic relationship of T. lepturus from the Persian Gulf using 16S rRNA sequences, and suggested homogeneity between Persian Gulf and the other Indo-Pacific individuals. However, Lin et al (2021) found that the specimens in Jahromi et al (2016) were identified as T. japonicus, T. lepturus, and T. nanhaiensis and the specimens in the Persian Gulf was nested with T. nanhaiensis using 16S rRNA sequences. Besides, Lin et al (2021) found T. nanhaiensis could be divide as two groups, Indo-Pacific and West Indian.…”
Section: Systematics Of Trichiurusmentioning
confidence: 99%
See 1 more Smart Citation
“…In the NW Pacific, T . japonicus has the widest distribution range compared to its congeners [ 6 ] and has been reported as the dominant cutlassfish species [ 7 , 112 ], with an estimated effective population size per location of around ~20,000. In addition, Hsu et al (2007) proposed that the high genotypic differentiation among cohorts is the underlying mechanism for the genetic diversity in cutlassfish [ 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…Population genetics of T . japonicus have only been studied using mitochondrial DNA markers, including cytochrome b (Cyt- b ) [ 20 , 25 ], control region (D-loop) [ 26 ], and 16S rRNA [ 6 ] gene regions. Although there is a general pattern of homogeneity and lack of intra-specific differentiation, only one study based on Cyt- b and control region revealed two genetically differentiated populations at the East and South China Seas, with Taiwan Strait as their transient zone [ 20 ].…”
Section: Introductionmentioning
confidence: 99%